Molecular Mechanisms and Clinical Divergences in HPV-Positive Cervical vs. Oropharyngeal Cancers: A Critical Narrative Review - Canio Martinelli; Alfredo Ercoli; Silvana Parisi; Giuseppe Iatì; Stefano Pergolizzi; Luigi Alfano; Francesca Pentimalli; Michelino De Laurentiis; Antonio Giordano; Salvatore Cortellino (BMC Medicine)
Abstract Human papillomavirus (HPV) plays a pivotal role in the development of both cervical squamous cell carcinoma (CSCC) and oropharyngeal squamous cell carcinoma (OPSCC). However, these two cancers exhibit markedly different clinical behaviors. While HPV-positive OPSCC is distinguished by its heightened radiosensitivity, enabling effective treatment de-escalation and reduced toxicity, HPV-positive CSCC shows no such advantage, requiring aggressive therapeutic approaches similar to HPV-negative cases. This critical narrative review explores the limited molecular drivers currently known and the potential mechanisms underlying the divergent clinical responses of HPV-positive OPSCC and CSCC. Here, we discuss the role of HPV E6 and E7 oncoproteins in disrupting key tumor suppressor pathways, the impact of HPV DNA integration into the host genome, and the resulting genomic instability. By comparing the molecular mechanisms of these cancers, we aim to provide a comprehensive understanding of how these processes contribute to their distinct radiosensitivities and clinical outcomes. This review further highlights the gaps in the current research and proposes areas for future investigation, particularly in tailoring personalized treatment strategies for HPV-driven cancers. Understanding the differences in the molecular pathways that influence radiosensitivity in HPV-related cancers will not only enhance treatment strategies but also lead to improved patient outcomes and reduced treatment-associated toxicity.